Pre-season testing for sub-elite australian football players: a needs analysis and testing recommendations - Kropinski, R. (Journal of Australian Strength and Conditioning, 2020)
Strength and conditioning coaches are required to develop training programs that enhance athletic development. To achieve this, coaches can assess athletes to identify their physical abilities and areas for improvement so that appropriate training is prescribed. The purpose of this paper is to present a needs analysis of Australian Rules and provide testing options, with current guidelines, for pre-season in Australian Football. A range of reliable and valid tests are recommended when assessing Australian Football athletes. These include height, with a typical error (TE) of 1%, body mass and skinfolds, in which excess can impeded performance, with TEs of 1.5% and 3% respectively. The countermovement jump, which tests power, should also be included and has a TE of 1.4cm and Interclass Correlation (ICC) of 0.96. Speed, a measure of acceleration, has a TE of 0.03s and ICC of 0.97. To test repeated supramaximal efforts, which are a feature of the game, either the 30-15IFT or the 2k time trial should be used. The 30-15IFT has a 0.3 km hr-1 TE and ICC of 0.96 whereas the 2k time trial has a 0% bias to the Montreal track Test which has a Pearson`s R of 0.97. Maximal strength tests are recommended to include in the battery and, depending on the type of muscle, have a TE range of 1.25 - 5kg and ICC of 0.97. In conclusion, testing can generate feedback, aid the optimisation of the training program and monitor the return to play athletes. It is recommended that that within a pre-season Australian Footballers at the sub-elite level undertake tests on Body Composition, Speed, Power, Change of Direction speed, Aerobic and Anaerobic Endurance and Maximal Strength.